2020
DOI: 10.1177/0025802419892392
|View full text |Cite
|
Sign up to set email alerts
|

Injuries, death and vehicle airbag deployment

Abstract: Airbags are impact-activated safety devices which deploy from the interior of vehicles to protect occupants from trauma during crashes. Although airbags effectively reduce the risk of death and injury, this it is not without issues. For example, high-impact unbelted rigid-barrier testing in the USA led to the adoption of powerful, large airbags that were associated with numerous airbag-related deaths and injuries. In contrast, European designs were tested and certified in conjunction with the use of three-poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Airbags, for example, were found to be effective in reducing the risk of death and injury. 24 Meanwhile, a meta-analysis done by Olivier and Creighton (2017) 25 found that wearing a helmet when riding a bicycle reduces the odds of head injury, serious head injury, facial injury, and fatal head injury.…”
Section: Discussionmentioning
confidence: 99%
“…Airbags, for example, were found to be effective in reducing the risk of death and injury. 24 Meanwhile, a meta-analysis done by Olivier and Creighton (2017) 25 found that wearing a helmet when riding a bicycle reduces the odds of head injury, serious head injury, facial injury, and fatal head injury.…”
Section: Discussionmentioning
confidence: 99%
“…SF injuries may be caused by broken glass from the windscreen and windows [ 29 ] and penetrating injuries are caused by loose, airborne objects from inside the vehicle or external objects that enter the vehicle cabin during the collision [ 30 ]. Fatal penetrating injuries have also been reported from the malfunction and inappropriate deployment of airbags [ 31 , 32 ]. Impalement is a severe form of penetrating injury characterised by an object penetrating the body [ 27 ].…”
Section: Classification Of Deathsmentioning
confidence: 99%
“…However, traditional airbags generate a great impact force during the instantaneous inflation process. 23,24 This impact force often causes great damages to the child occupants with the non-standard sitting postures. Park and Hong 25 found that the great impact force during the airbag instantaneous inflation process, caused serious injuries to various body regions of the child occupants.…”
Section: Introductionmentioning
confidence: 99%